OECD countries' twin long-run challenge: The impact of aging dynamics and increasing natural disasters on savings ratios - Tian Xiong; Kaan Celebi; Paul J. J. Welfens (International Economics and Economic Policy, 2022)
There has been a long-standing debate over the development of savings rates in developed economies, and an emphasis has been placed on aging societies and a global savings glut. Meanwhile, with rising global temperatures and more frequent extreme weather events becoming an increasingly visible economic and ecological global challenge, the concern of climate-related risks could indeed be an important issue in monetary and real economic analysis. This study aims to investigate the dual long-term challenge of sustainable economic development. By constructing an enhanced growth model and investigating empirically, using a panel approach which employs data from OECD countries between 1980 and 2020, the question as to the extent to which the savings rate is affected by aging populations and environmental degradation will be addressed in a broad macro perspective. This study explores for the first time the impact of natural disasters on OECD countries and the main findings indicate that aging populations and natural disasters have significant negative impacts on savings rates. Moreover, the analyses using sub-samples suggest a diminishing role of the real long-term interest rate regarding savings behaviour.
Keywords: E21; E43; J11; O11; Q54; C33; 330; Savings rate; Aging; Natural disaster; Economic growth; Panel analysis; OECD